Graphite modified polystyrene bead and preparation method thereof
By adding graphite filler and antistatic agent to the polystyrene beads and subjecting antioxidant treatment, the problem of insufficient comprehensive performance of polystyrene beads is solved, and graphite modified polystyrene beads with high material yield, good flame retardant, heat resistance and mechanical properties are achieved.
Patent Information
- Application Number
- CN202510287185.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The comprehensive performance of existing polystyrene beads in the market cannot meet the ever-increasing market requirements, especially in terms of thermal insulation, flame retardant and mechanical properties.
By adding graphite filler and antistatic agent, and combining sodium dihydrogen phosphate, sodium tetraborate, cashew phenol surfactant and water, the graphite particles are subjected to antioxidant treatment, improving their high temperature resistance and antioxidant ability, and finally preparing graphite modified polystyrene beads.
The foam plate obtained by graphite modified polystyrene beads after foaming exhibits an ultimate oxygen index of more than 32.5%, a combustion performance level of B1, a thermal conductivity coefficient of no higher than 0.0273W/(m·K), a tensile strength of no lower than 0.279MPa and a compression strength of no lower than 0.24MPa, significantly improving its flame retardant performance, heat resistance and mechanical properties.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to graphite-modified polystyrene beads and a preparation method thereof. Background Art
[0002] Polystyrene (PS) is a polymer synthesized from styrene monomers by free radical addition polymerization. It has multiple properties and a wide range of uses. It has good chemical stability, is not easily corroded by acids, alkalis, solvents, etc., has good insulation properties and high hardness, rigidity and strength. Among the many PS, expandable polystyrene can be used as packaging materials for various instruments, valuables, precision instruments, vegetables, fruits and aquatic products, or as a heat-insulating fixture used in window frame installation in house construction because of its ability to expand and form a lightweight porous foam structure when heated.
[0003] At present, technicians use polystyrene as raw material and rely on suspension method and extrusion method to produce polystyrene beads, which improves the convenience of subsequent processing, transportation and sales. Among them, the extrusion method is widely used due to its high yield rate. However, as the market's requirements for material performance continue to increase, the comprehensive performance of polystyrene beads produced by extrusion has also been subject to higher requirements. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a graphite-modified polystyrene bead and a preparation method thereof.
[0005] In the first aspect, the present application provides a graphite-modified polystyrene bead, which adopts the following technical scheme: the raw materials used include the following components in parts by weight: 2-3 parts of graphite filler; 1-1.25 parts of flame retardant; 0.5-0.8 parts of antioxidant; 0.05-0.08 parts of lubricant; 0.25-0.5 parts of nucleating agent; 3-4 parts of pentane; 40-50 parts of antistatic agent; 85-95 parts of general-purpose polystyrene; the graphite filler is prepared by the following method: graphite particles are immersed in a pretreatment liquid at a solid-liquid ratio of 1: (10-12), and heat-treated for 60-75 minutes to obtain a graphite filler, wherein the pretreatment liquid includes sodium dihydrogen phosphate, sodium tetraborate, cardanol surfactant and water in a weight ratio of 10: (8-12): 6.5: 100.
[0006] By adopting the above technical scheme, the present application first adds a graphite filler with excellent heat resistance, high flame retardancy and strong mechanical stability into the system, improves the thermal insulation, flame retardancy and mechanical properties of the polystyrene beads, and uses sodium dihydrogen phosphate, sodium tetraborate, cardanol surfactant and water to compound to obtain a pretreatment solution, and the graphite particles are subjected to antioxidant treatment. The graphite filler finally obtained has better high temperature resistance and antioxidant ability, so that the graphite-modified polystyrene beads have better flame retardancy, heat resistance and mechanical properties. The cardanol surfactant of the present application can further promote the enhancement of the immersion wettability between the pretreatment solution and the graphite particles, so that the effective components (sodium dihydrogen phosphate, sodium tetraborate) in the pretreatment can better adhere to the surface of the graphite particles and penetrate into the internal pores of the graphite particles, thereby promoting the strengthening of the antioxidant ability of the graphite particles. More importantly, compared with other surfactants (sodium dodecylbenzene sulfonate or alcohol ether sulfate), the cardanol surfactant of the present application has higher stability and lower critical micelle concentration, and also has a better ability to promote the degree of wetting.
[0007] At the same time, the present application also adds antistatic agents to perform antistatic treatment on polystyrene, thereby reducing the possibility of static electricity generated in the final product during pre-expansion, helping the product to completely eliminate foam particles, making its pre-expansion more stable, thereby improving product quality, and finally ensuring the molding density and strength of the foam board obtained after foaming.
[0008] In general, the graphite-modified polystyrene beads of the present application contain graphite fillers with good antioxidant ability, excellent heat resistance, high flame retardant performance and strong mechanical stability, and are assisted by antistatic agents for coating treatment. In addition, the present application uses additional additives such as flame retardants, antioxidants, lubricants, nucleating agents, etc., and after a series of preparation treatments, graphite-modified polystyrene beads with good flame retardant performance, heat resistance and mechanical properties are finally obtained. The limiting oxygen index of the foam board obtained after foaming can reach more than 32.5%, the combustion performance level can reach B1, the thermal conductivity is not higher than 0.0273W / (m·K), the tensile strength is not less than 0.279MPa, and the compressive strength is not less than 0.24MPa.
[0009] Among them, flame retardants, antioxidants, lubricants, and nucleating agents are any one or more of commercially available models. In the specific implementation of the present application, only methyl octabromoether and tricresyl phosphate are used as flame retardants, antioxidants 168 and antioxidants 1076 are used as antioxidants, N,N'-ethylene bisstearamide is used as a lubricant, and N,N-dimethyl-1,3-propylenediamine is used as a nucleating agent for illustration. However, this does not limit the scope of protection of the present application. In actual use, those skilled in the art can make reasonable adjustments according to actual conditions.
[0010] Preferably, the weight ratio of the sodium dihydrogen phosphate, sodium tetraborate, cardanol surfactant and water is 10:10:5:100.
[0011] By adopting the above technical scheme, the present application further controls the weight ratio of sodium dihydrogen phosphate, sodium tetraborate, cardanol surfactant and water, thereby optimizing the degree of improvement of the antioxidant capacity of graphite particles by the pretreatment liquid. Experimental data show that the limiting oxygen index, combustion performance level, compressive strength and tensile strength of the foam board obtained by the graphite-modified polystyrene beads after foaming are all improved.
[0012] Preferably, the heat treatment time is divided into three sections, and the temperature is raised in sequence in each section. The specific operation is: after the graphite particles are immersed in the pretreatment solution, the temperature is raised to 200°C at a heating rate of 40-45°C / min and then allowed to stand, which is the first section, then the temperature is raised to 300°C at a heating rate of 20-25°C / min and then allowed to stand, which is the second section, and finally the temperature is raised to 400°C at a heating rate of 20-25°C / min and then allowed to stand, which is the third section.
[0013] By adopting the above technical solution, the present application divides the heat treatment time into three sections, and raises the temperature in each section in turn, which can significantly enhance the immersion and wetting degree between the pretreatment liquid and the graphite particles, allowing the effective components in the pretreatment to better adhere to the surface of the graphite particles and penetrate into the internal pores of the graphite particles, thereby promoting the enhancement of the antioxidant capacity of the graphite particles.
[0014] Preferably, the preparation method of the cardanol surfactant comprises the following steps: I. acidifying and ring-opening cardanol glycidyl ether to obtain cardanol chlorohydrin ether; II. mixing a tertiary amine and cardanol chlorohydrin ether in a molar ratio of (12-15):10, carrying out a condensation reaction at a temperature of 45-60°C for 6-12h, removing impurities, washing, and rotary evaporation to obtain a cardanol surfactant, wherein the tertiary amine is any one of 3-diethylamino-1,2-propylene glycol and 3-diethylamino-1-propanol.
[0015] Preferably, in step II, the condensation reaction temperature is 50° C. and the condensation reaction time is 8 h.
[0016] Preferably, in step II, the tertiary amine is 3-diethylamino-1,2-propylene glycol.
[0017] By adopting the above technical scheme, the present application uses cardanol glycidyl ether as a raw material, first performs acidification and ring opening, and then performs condensation reaction with tertiary amine to obtain a cardanol surfactant with low critical micelle concentration, strong emulsification and high solubilization, and cardanol has the advantages of green renewable, degradable, low toxicity and low cost, so the cardanol surfactant of the present application can not only effectively promote the immersion and wetting degree between the pretreatment liquid and the graphite particles, but also has certain environmental significance. In addition, the present application strictly controls the temperature and time of the condensation reaction, effectively improves the conversion rate of the cardanol surfactant, and uses 3-diethylamino-1,2-propylene glycol as a tertiary amine to condense with the ring-opening product, thereby further optimizing the emulsification and solubilization ability of the cardanol surfactant.
[0018] Preferably, the preparation method of the antistatic agent comprises the following steps: dispersing sodium polystyrene sulfonate and dodecyltrimethylammonium bromide in an aqueous polyurethane emulsion, stirring until the system is in a uniform state, and obtaining the antistatic agent, wherein the weight ratio of the sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and the aqueous polyurethane emulsion is 1:1:(6-9).
[0019] By adopting the above technical solution, the present application uses sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and waterborne polyurethane to prepare an antistatic agent with high adhesion, good thermal stability and processing stability, thereby improving the product quality of graphite-modified polystyrene beads. In addition, the present application also controls the weight ratio of sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and waterborne polyurethane emulsion, and balances the stability and antistatic ability of the antistatic agent as much as possible. If the amount of waterborne polyurethane emulsion is too large, the antistatic ability of the antistatic agent will be greatly reduced. If the amount of waterborne polyurethane emulsion is too small, the adhesion ability of the antistatic agent will be weakened, and it will not be able to achieve a close combination effect with the polystyrene beads.
[0020] Preferably, the weight ratio of the sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and aqueous polyurethane emulsion is 1:1:8.
[0021] By adopting the above technical solution, the weight ratio of sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and aqueous polyurethane emulsion is strictly controlled to be 1:1:8. Experimental data show that at this time, the stability and antistatic ability of the antistatic agent reach the optimal balance, and the quality improvement effect on the polystyrene beads is optimal. Finally, the tensile strength and compressive strength of the foamed board formed after foaming are improved.
[0022] In the second aspect, the present application provides a method for preparing graphite-modified polystyrene beads, comprising the following steps: charging graphite filler, flame retardant, antioxidant, lubricant, nucleating agent, pentane and general polystyrene, then mixing the ingredients, melt-extruding, decompressing, pelletizing, cooling, drying, screening, and coating with an antistatic agent to obtain graphite-modified polystyrene beads, wherein the melting temperature during melt extrusion is 175-190°C.
[0023] By adopting the above technical scheme, the present application first prepares the raw materials except the antistatic agent, mixes them according to weight parts, and then feeds them into an extruder for melt extrusion at a temperature of 175-190°C to ensure that the raw materials are fully melted and maintain the performance of the graphite filler. The pressure is then reduced to remove the air or volatile substances in the raw materials to avoid the formation of bubbles or holes in the finished product as much as possible. After the molten material is extruded through the die head of the extruder, it is immediately cut into beads. In the present application, this process is carried out in water to quickly cool and solidify the beads. The beads are then further cooled to ensure that their shape is stable, dried, and the surface and internal moisture is removed. Beads of unqualified size or shape are screened. Finally, the screened beads are coated to improve their antistatic properties. After a series of preparation processes, the present application finally obtains graphite-modified polystyrene beads with a high yield rate and good flame retardant properties, heat resistance and mechanical properties.
[0024] In summary, this application has the following beneficial technical effects: 1. The graphite-modified polystyrene beads of the present application contain graphite fillers with good antioxidant ability, excellent heat resistance, high flame retardancy and strong mechanical stability, and are coated with antistatic agents. In addition, the present application uses additional additives such as flame retardants, antioxidants, lubricants, and nucleating agents, and finally obtains graphite-modified polystyrene beads with good flame retardancy, heat resistance and mechanical properties. The limiting oxygen index of the foamed board obtained after foaming can reach more than 32.5%, the combustion performance level can reach B1, the thermal conductivity is not higher than 0.0273W / (m·K), the tensile strength is not less than 0.279MPa, and the compressive strength is not less than 0.24MPa; 2. This application uses sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and water-based polyurethane to prepare an antistatic agent with high adhesion, good thermal stability and processing stability, thereby improving the product quality of graphite-modified polystyrene beads; 3. After a series of preparation processes, the present application finally obtains graphite-modified polystyrene beads with high yield rate and good flame retardant properties, heat resistance and mechanical properties. DETAILED DESCRIPTION
[0025] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Cardanol glycidyl ether, CAS number is 171263-25-5; 3-Diethylamino-1-propanol, CAS number is 156-87-6; 3-Diethylamino-1,2-propanediol, CAS number is 621-56-7; Silane coupling agent was purchased from Shandong Huachen New Materials Co., Ltd., KH-570; Graphite particles were purchased from Hebei Ruitong Carbon Co., Ltd., with a carbon content of 95%. They were first polished with sandpaper, the powder on the surface was washed with water, the surface moisture was wiped dry with absorbent paper, and then washed with alcohol for 6 minutes, and then dried at 100°C to constant weight for use; Waterborne polyurethane was purchased from DCH Chemical International Trading (Shanghai) Co., Ltd.; The silicone surfactant was purchased from BASF with the product number WE-3229; Sodium polystyrene sulfonate, CAS number is 25704-18-1; Dodecyltrimethylammonium bromide, CAS number is 1119-94-4; Sodium dodecylbenzenesulfonate, CAS number is 25155-30-0; Alcohol ether sulfate was purchased from BASF with the product number Disponil FES 77; Methyl octabromoether, CAS number is 97416-84-7; Tricresyl phosphate, CAS number is 1330-78-5; Antioxidant 168 and antioxidant 1076 were purchased from Dongguan Xingyuan Chemical Co., Ltd.; N,N'-ethylenebisstearamide, CAS number is 110-30-5; N,N-Dimethyl-1,3-propylenediamine, CAS number is 109-55-7.
[0026] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0027] Preparation Example 1.1 The preparation method of the cardanol surfactant comprises the following steps: Under continuous stirring in an ice-water bath, a 1:1 volume ratio of cardanol glycidyl ether-ether solution was slowly added dropwise to 1.1 kg of 37 wt % hydrochloric acid, wherein the amount of cardanol glycidyl ether was 3.6 kg, and then the temperature was raised to 35 ° C. The reaction progress was monitored by thin layer chromatography. After the cardanol glycidyl ether was completely consumed, the pH of the solution was adjusted to neutral with NaOH, and the stratification was allowed to stand. The aqueous layer was extracted three times with ether, the ether layers were combined, and the ether was distilled off after drying with anhydrous sodium sulfate to obtain a yellow-brown viscous liquid, which was cardanol chlorohydrin ether; 3-diethylamino-1-propanol was dispersed in water, and the cardanol chlorohydrin ether obtained in step I was dispersed in ethanol. The cardanol chlorohydrin ether ethanol solution and 30% sodium hydroxide solution were simultaneously added dropwise to the tertiary amine aqueous solution until the molar ratio of 3-diethylamino-1-propanol, cardanol chlorohydrin ether and sodium hydroxide in the system was 12:10:14. The condensation reaction was carried out at a temperature of 60° C. for 12 hours, and the pH of the solution was adjusted to neutral with hydrochloric acid. The solvent was removed under reduced pressure, and cold methanol was added to remove the sodium chloride generated by the reaction. After removing most of the methanol under reduced pressure, n-hexane was added for washing and separation. The solvent was removed by rotary evaporation at the lower layer to obtain a cardanol surfactant. The conversion rate was 78.5% after detection.
[0028] Preparation Example 1.2 The preparation method of the cardanol surfactant comprises the following steps: Under continuous stirring in an ice-water bath, a 1:1 volume ratio of cardanol glycidyl ether-ether solution was slowly added dropwise to 1.1 kg of 37 wt % hydrochloric acid, wherein the amount of cardanol glycidyl ether was 3.6 kg, and then the temperature was raised to 35 ° C. The reaction progress was monitored by thin layer chromatography. After the cardanol glycidyl ether was completely consumed, the pH of the solution was adjusted to neutral with NaOH, and the stratification was allowed to stand. The aqueous layer was extracted three times with ether, the ether layers were combined, and the ether was distilled off after drying with anhydrous sodium sulfate to obtain a yellow-brown viscous liquid, which was cardanol chlorohydrin ether; 3-diethylamino-1-propanol was dispersed in water, and the cardanol chlorohydrin ether obtained in step I was dispersed in ethanol. The cardanol chlorohydrin ether ethanol solution and 30% sodium hydroxide solution were simultaneously added dropwise to the tertiary amine aqueous solution until the molar ratio of 3-diethylamino-1-propanol, cardanol chlorohydrin ether and sodium hydroxide in the system was 15:10:14. The condensation reaction was carried out at a temperature of 45° C. for 6 hours, and the pH of the solution was adjusted to neutral with hydrochloric acid. The solvent was removed under reduced pressure, and cold methanol was added to remove the sodium chloride generated by the reaction. After removing most of the methanol under reduced pressure, n-hexane was added for washing and separation. The solvent was removed by rotary evaporation at the lower layer to obtain a cardanol surfactant. The conversion rate was 82.3% after detection.
[0029] Preparation Example 1.3 The preparation method of the cardanol surfactant is different from that of Preparation Example 1.1 in that: in step II, the condensation reaction temperature is 50°C, the condensation reaction time is 8h, and the rest is the same as Preparation Example 1.1. The obtained cardanol surfactant has a conversion rate of 97.8% after testing.
[0030] Preparation Example 1.4 The preparation method of the cardanol surfactant is different from that of Preparation Example 1.1 in that: in step II, the condensation reaction temperature is 40°C, the condensation reaction time is 15h, and the rest is the same as Preparation Example 1.1. The conversion rate of the obtained cardanol surfactant is 64.3% after testing.
[0031] Preparation Example 1.5 The preparation method of the cardanol surfactant is different from that of Preparation Example 1.1 in that: in step II, the condensation reaction temperature is 65° C., the condensation reaction time is 6 hours, and the rest is the same as Preparation Example 1.1. The obtained cardanol surfactant has a conversion rate of 62.7% after testing.
[0032] Preparation Example 1.6 The preparation method of the cardanol surfactant is different from that of Preparation Example 1.3 in that 3-diethylamino-1-propanol is replaced by 3-diethylamino-1,2-propylene glycol, and the rest is the same as Preparation Example 1.1. The conversion rate of the obtained cardanol surfactant is 97.5% after testing.
[0033] Preparation Example 2.1 The preparation method of graphite filler comprises the following steps: 7.5 kg of sodium dihydrogen phosphate was put into 100 L of water and stirred until it was completely dissolved. Then 2.5 kg of sodium dihydrogen phosphate was added and stirred until the system was transparent with no residual impurities. Then 8 kg of sodium tetraborate was added into the system and stirred until it was completely dissolved. The system was transparent with no residual impurities. Finally, 6.5 kg of the cardanol surfactant prepared in Preparation Example 1.1 was added and stirred evenly to obtain a pretreatment solution. The treated graphite particles were immersed in the pretreatment solution at a solid-liquid ratio of 1:10, heat treated for 75 min, then naturally cooled to room temperature, and washed with alcohol for 10 min to obtain a graphite filler.
[0034] Preparation Example 2.2 The preparation method of graphite filler comprises the following steps: 7.5 kg of sodium dihydrogen phosphate was put into 100 L of water and stirred thoroughly until it was completely dissolved. Then, 2.5 kg of sodium dihydrogen phosphate was added and stirred thoroughly until the system was transparent with no residual impurities. Then, 12 kg of sodium tetraborate was added into the system and stirred until it was completely dissolved. The system was transparent with no residual impurities. Finally, 6.5 kg of the cardanol surfactant prepared in Preparation Example 1.2 was added and stirred evenly to obtain a pretreatment solution. The treated graphite particles were immersed in the pretreatment solution at a solid-liquid ratio of 1:12, heat treated for 60 min, then naturally cooled to room temperature, and washed with alcohol for 10 min to obtain a graphite filler.
[0035] Preparation Example 2.3 The preparation method of graphite filler is different from that of Preparation Example 2.1 in that the amount of sodium tetraborate used is 10 kg, and the rest is the same as that of Preparation Example 2.1.
[0036] Preparation Example 3.1 The preparation method of graphite filler is different from that of Preparation Example 2.1 in that the heat treatment time is divided into three sections of 25 minutes, and the temperature is raised in sequence in each section. The specific operation is: the treated graphite particles are immersed in the pretreatment liquid at a solid-liquid ratio of 1:10, the temperature is raised to 200°C at a heating rate of 45°C / min and then allowed to stand, the total heating and standing time is 25 minutes, then the temperature is raised to 300°C at a heating rate of 20°C / min and then allowed to stand, the total heating and standing time is 25 minutes, and finally the temperature is raised to 400°C at a heating rate of 20°C / min and then allowed to stand, the total heating and standing time is 25 minutes.
[0037] Preparation Example 3.2 The preparation method of graphite filler is different from that of Preparation Example 2.1 in that the heat treatment time is divided into three sections of 25 minutes, and the temperature is raised in sequence in each section. The specific operation is: the treated graphite particles are immersed in the pretreatment liquid at a solid-liquid ratio of 1:10, the temperature is raised to 200°C at a heating rate of 40°C / min and then allowed to stand, the total heating and standing time is 25 minutes, then the temperature is raised to 300°C at a heating rate of 25°C / min and then allowed to stand, the total heating and standing time is 25 minutes, and finally the temperature is raised to 400°C at a heating rate of 25°C / min and then allowed to stand, the total heating and standing time is 25 minutes.
[0038] Preparation Examples 4.1-4.3 The preparation method of graphite filler is different from that of Preparation Example 2.1 in that the cardanol surfactant prepared in Preparation Example 1.1 is replaced by the cardanol surfactants prepared in Preparation Examples 1.3-1.5 respectively, and the rest is the same as Preparation Example 2.1.
[0039] Preparation Example 4.4 The preparation method of graphite filler is different from that of Preparation Example 4.1 in that the cardanol surfactant prepared in Preparation Example 1.3 is replaced by the cardanol surfactant prepared in Preparation Example 1.6, and the rest is the same as Preparation Example 4.1.
[0040] Preparation Example 5.1 The preparation method of the antistatic agent comprises the following steps: Weigh aqueous polyurethane, silane coupling agent, isopropyl alcohol, silicone surfactant and water in a weight ratio of 5:0.5:2:1.2:20, mix and stir evenly to obtain an aqueous polyurethane emulsion, then disperse 1 kg of sodium polystyrene sulfonate and 1 kg of dodecyltrimethylammonium bromide in 6 kg of the aqueous polyurethane emulsion, stir until the system is uniform, and obtain an antistatic agent.
[0041] Preparation Example 5.2 The preparation method of the antistatic agent comprises the following steps: Weigh aqueous polyurethane, silane coupling agent, isopropyl alcohol, silicone surfactant and water in a weight ratio of 5:0.5:2:1.2:20, mix and stir evenly to obtain an aqueous polyurethane emulsion, then disperse 1 kg of sodium polystyrene sulfonate and 1 kg of dodecyltrimethylammonium bromide in 9 kg of the aqueous polyurethane emulsion, stir until the system is uniform, and obtain an antistatic agent.
[0042] Preparation Example 5.3 The preparation method of the antistatic agent is different from that of Preparation Example 5.1 in that 1 kg of sodium polystyrene sulfonate and 1 kg of dodecyltrimethylammonium bromide are dispersed in 7 kg of aqueous polyurethane emulsion and stirred until the system is uniform to obtain the antistatic agent.
[0043] Preparation Example 5.4 The preparation method of the antistatic agent is different from that of Preparation Example 5.1 in that 1 kg of sodium polystyrene sulfonate and 1 kg of dodecyltrimethylammonium bromide are dispersed in 8 kg of aqueous polyurethane emulsion and stirred until the system is uniform to obtain the antistatic agent.
[0044] Comparative Preparation Example 1 The preparation method of graphite filler is different from that of Preparation Example 2.1 in that the cardanol surfactant prepared in Preparation Example 1.1 is replaced with sodium dodecylbenzene sulfonate, and the rest is the same as Preparation Example 2.1.
[0045] Comparative Preparation Example 2 The preparation method of graphite filler is different from that of Preparation Example 2.1 in that the cardanol surfactant prepared in Preparation Example 1.1 is replaced with alcohol ether sulfate, and the rest is the same as Preparation Example 2.1.
[0046] Example 1.1 A method for preparing graphite-modified polystyrene beads comprises the following steps: S1. Loading: Pour the graphite filler, flame retardant, antioxidant, lubricant, nucleating agent, pentane and general-purpose polystyrene prepared in Preparation Example 2.1 into the corresponding feeding station hoppers, perform positive pressure and negative pressure system loading, and transport the materials to the receiving hoppers through the sending tanks; S2. Batching and mixing: The batching is controlled by the central control, and the materials in the receiving hopper are respectively transported to the weighing scale, and the ingredients are automatically batched according to the required addition amount. The addition amount is shown in Table 1; S3, melt extrusion and decompression: the material is fed to the melt pump through a loss-in-weight scale, the melt temperature is set to 175°C, the melt pump speed is set to 80r / min, and then the pressure is reduced and the exhaust is exhausted; S4, pelletizing: The material is transported to the pelletizer, extruded through a twin-screw extruder, and cut into material particles by a pelletizer. The temperature of the template oil temperature machine is set at 250°C, and the speed of the cutter is set at 800r / min; S5, drying: the material particles are dehydrated and dried in the centrifugal dryer from the pelletizing chamber; S6, screening: the dried material is transported to the screening machine; S7, coating: the sieved material is coated, and the antistatic agent used in the coating is the antistatic agent prepared in Preparation Example 5.1, and the amount used is shown in Table 1; S8, finished product: the coated material is sent to the finished product tank through a conveying pipeline to obtain graphite modified polystyrene beads.
[0047] Example 1.2 A method for preparing graphite-modified polystyrene beads comprises the following steps: S1. Loading: Pour the graphite filler, flame retardant, antioxidant, lubricant, nucleating agent, pentane and general-purpose polystyrene prepared in Preparation Example 2.2 into the corresponding feeding station hoppers, perform positive pressure and negative pressure system loading, and transport the materials to the receiving hoppers through the sending tanks; S2. Batching and mixing: The batching is controlled by the central control, and the materials in the receiving hopper are respectively transported to the weighing scale, and the ingredients are automatically batched according to the required addition amount. The addition amount is shown in Table 1; S3, melt extrusion and decompression: the material is fed to the melt pump through a loss-in-weight scale, the melt temperature is set to 190°C, the melt pump speed is set to 80r / min, and then the pressure is reduced and the exhaust is exhausted; S4, pelletizing: The material is transported to the pelletizer, extruded through a twin-screw extruder, and cut into material particles by a pelletizer. The temperature of the template oil temperature machine is set at 250°C, and the speed of the cutter is set at 800r / min; S5, drying: the material particles are dehydrated and dried in the centrifugal dryer from the pelletizing chamber; S6, screening: the dried material is transported to the screening machine; S7, coating: the sieved material is coated, and the antistatic agent used in the coating is the antistatic agent prepared in Preparation Example 5.2, and the amount used is shown in Table 1; S8, finished product: the coated material is sent to the finished product tank through a conveying pipeline to obtain graphite modified polystyrene beads.
[0048] Table 1 Raw material dosage / kg of Examples 1.1-1.2
[0049] Example 1.3 A method for preparing graphite-modified polystyrene beads, which is different from Example 1.1 in that, in step S1, the graphite filler prepared in Preparation Example 2.1 is replaced by the graphite filler prepared in Preparation Example 2.3, and the rest is the same as Example 1.1.
[0050] Examples 2.1-2.2 A method for preparing graphite-modified polystyrene beads, which is different from Example 1.1 in that, in step S1, the graphite fillers prepared in Preparation Example 2.1 are replaced by the graphite fillers prepared in Preparation Examples 3.1-3.2 respectively, and the rest are the same as Example 1.1.
[0051] Examples 3.1-3.3 A method for preparing graphite-modified polystyrene beads, which is different from Example 1.1 in that, in step S1, the graphite filler prepared in Preparation Example 2.1 is replaced by the graphite fillers prepared in Preparation Examples 4.1-4.3 respectively, and the rest is the same as Example 1.1.
[0052] Example 4
[0053] A method for preparing graphite-modified polystyrene beads, which is different from Example 3.1 in that, in step S1, the graphite filler prepared in Preparation Example 4.1 is replaced by the graphite filler prepared in Preparation Example 4.4, and the rest is the same as Example 3.1.
[0054] Examples 5.1-5.2 A method for preparing graphite-modified polystyrene beads, which is different from Example 1.1 in that, in step S7, the antistatic agent prepared in Preparation Example 5.1 is replaced by the antistatic agents prepared in Preparation Examples 5.3-5.4 respectively, and the rest is the same as Example 1.1.
[0055] Comparative Example 1 The difference from Example 1.1 is that in step S1, the graphite filler prepared in Preparation Example 2.1 is replaced by graphite particles without any treatment, and the rest is the same as Example 1.1.
[0056] Comparative Examples 2.1-2.2 The difference from Example 1.1 is that in step S1, the graphite fillers prepared in Preparation Example 2.1 are replaced by the graphite fillers prepared in Comparative Preparation Examples 1-2 respectively, and the rest are the same as Example 1.1.
[0057] Performance Testing 1. Limiting oxygen index: The graphite-modified polystyrene beads obtained in the examples and comparative examples were made into standard samples according to GB / T 3399-1982, and then tested according to the records in GB / T 2406.2-2009. The specific experimental data are shown in Table 2; 2. Combustion performance test: The graphite-modified polystyrene beads obtained in the examples and comparative examples were made into standard samples according to GB / T3399-1982, and then the samples were graded according to the records in GB 8624-2012. The results are shown in Table 2; 3. Thermal conductivity: The graphite-modified polystyrene beads obtained in the examples and comparative examples were made into standard samples according to GB / T 3399-1982, and their thermal conductivity (W / (m·K)) was tested using the guarded hot plate method. The specific experimental data are shown in Table 2; 4. Tensile strength: According to the record in GB 9641-1988, a dumbbell-shaped foam board was made and the tensile performance test was carried out using a testing machine at 25°C. The fixture moving speed was 5±1mm / min. The specific experimental data are shown in Table 2; 5. Compression strength: The graphite-modified polystyrene beads obtained in the examples and comparative examples were made into standard specimens according to GB / T 3399-1982, and their compression strength at a deformation of 10% was measured according to the record in GB / T8813-2020. The specific experimental data are shown in Table 2.
[0058] Table 2 Performance test table
[0059] Data Analysis: As can be seen from Table 2, the limiting oxygen index of the foam board made from the graphite-modified polystyrene beads of Examples 1.1-1.2 of the present application can reach 32.5-32.6%, the combustion performance level can reach B1, the thermal conductivity is 0.0271-0.0273 W / (m·K), the tensile strength is 0.279 MPa, and the compressive strength is 0.24-0.242 MPa, which proves that the graphite-modified polystyrene beads of the present application contain graphite fillers with good antioxidant ability, excellent heat resistance, high flame retardant performance and strong mechanical stability, and are assisted by antistatic agents for coating treatment. In addition, the present application uses additional additives such as flame retardants, antioxidants, lubricants, nucleating agents, etc., and after a series of preparation treatments, graphite-modified polystyrene beads with good flame retardant performance, heat resistance and mechanical properties are finally obtained; The data of Example 1.3 are all better than those of Example 1.1, which proves that the present application can optimize the degree of improvement of the antioxidant capacity of graphite particles by the pretreatment liquid by controlling the weight ratio of sodium dihydrogen phosphate, sodium tetraborate, cardanol surfactant and water. At this time, the limiting oxygen index, combustion performance level, compressive strength and tensile strength of the foam board obtained by the graphite-modified polystyrene beads after foaming are all improved; The data of Examples 2.1-2.2 are better than those of Example 1.1, which proves that the present application can significantly enhance the degree of immersion and wetting between the pretreatment liquid and the graphite particles by dividing the heat treatment time into three sections and sequentially raising the temperature in each section, so that the effective components in the pretreatment can better adhere to the surface of the graphite particles and penetrate into the internal pores of the graphite particles, thereby promoting the enhancement of the antioxidant capacity of the graphite particles; All the data of Example 4 are better than those of Example 1.1, which proves that the present application further optimizes the emulsification and solubilization ability of the cardanol surfactant by using 3-diethylamino-1,2-propylene glycol as a tertiary amine to condense with the ring-opening product; The thermal conductivity of Example 5.2 is lower than that of Example 1.1 and Example 5.1, and the tensile strength and compressive strength are higher than those of Example 1.1 and Example 5.1, which proves that the present application balances the stability and antistatic ability of the antistatic agent as much as possible by controlling the weight ratio of sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and aqueous polyurethane emulsion. If the amount of aqueous polyurethane emulsion is too large, the antistatic ability of the antistatic agent will be greatly reduced. If the amount of aqueous polyurethane emulsion is too small, the adhesion ability of the antistatic agent will be weakened, and it will not be able to achieve a close bonding effect with the polystyrene beads. The data of Comparative Example 1 are all inferior to those of Example 1.1, which proves that the present application uses sodium dihydrogen phosphate, sodium tetraborate, cardanol surfactant and water to prepare a pretreatment solution, and uses the pretreatment solution to treat the graphite particles with antioxidants, so that the final graphite filler has better high temperature resistance and antioxidant ability, and the graphite-modified polystyrene beads have better flame retardancy, heat resistance and mechanical properties. The data of Comparative Examples 2.1-2.2 are all inferior to those of Example 1.1, which proves that the cardanol surfactant of the present application can further promote the enhancement of the immersion wettability between the pretreatment liquid and the graphite particles, so that the sodium dihydrogen phosphate and sodium tetraborate in the pretreatment can better adhere to the surface of the graphite particles and penetrate into the internal pores of the graphite particles, thereby promoting the enhancement of the antioxidant capacity of the graphite particles. More importantly, compared with other surfactants, the cardanol surfactant of the present application has higher stability and lower critical micelle concentration, and thus has a better ability to promote immersion wettability.
[0060] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A graphite-modified polystyrene bead, characterized in that: The raw materials used include the following components in parts by weight: 2-3 parts of graphite filler; 1-1.25 parts of flame retardant; 0.5-0.8 parts of antioxidant; 0.05-0.08 parts of lubricant; 0.25-0.5 parts of nucleating agent; 3-4 parts of pentane; 40-50 parts of antistatic agent; 85-95 parts of general-purpose polystyrene; the graphite filler is prepared by the following method: The graphite particles are immersed in a pretreatment solution at a solid-liquid ratio of 1:(10-12), and heat treated for 60-75 minutes to obtain a graphite filler. The pretreatment solution includes sodium dihydrogen phosphate, sodium tetraborate, cardanol surfactant and water at a weight ratio of 10:(8-12):6.5:
100.
2. The graphite-modified polystyrene beads according to claim 1, characterized in that: The weight ratio of the sodium dihydrogen phosphate, sodium tetraborate, cardanol surfactant and water is 10:10:6.5:
100.
3. The graphite-modified polystyrene beads according to claim 1, characterized in that: The heat treatment time is divided into three sections, and the temperature is raised in sequence in each section. The specific operation is as follows: After the graphite particles are immersed in the pretreatment solution, the temperature is increased to 200°C at a heating rate of 40-45°C / min and then allowed to stand, which is the first period of time. Subsequently, the temperature is increased to 300°C at a heating rate of 20-25°C / min and then allowed to stand, which is the second period of time. Finally, the temperature is increased to 400°C at a heating rate of 20-25°C / min and then allowed to stand, which is the third period of time.
4. The graphite-modified polystyrene beads according to claim 1, characterized in that: The preparation method of the cardanol surfactant comprises the following steps:
1. Acidifying and ring-opening cardanol glycidyl ether to obtain cardanol chlorohydrin ether; II. Mix a tertiary amine and cardanol chlorohydrin ether in a molar ratio of (12-15):10, carry out condensation reaction at a temperature of 45-60°C for 6-12 hours, remove impurities, wash, and rotary evaporate to obtain a cardanol surfactant, wherein the tertiary amine is any one of 3-diethylamino-1,2-propylene glycol and 3-diethylamino-1-propanol.
5. The graphite-modified polystyrene beads according to claim 4, characterized in that: In the step II, the condensation reaction temperature is 50° C., and the condensation reaction time is 8 hours.
6. The graphite-modified polystyrene beads according to claim 5, characterized in that: In the step II, the tertiary amine is 3-diethylamino-1,2-propylene glycol.
7. The graphite-modified polystyrene beads according to claim 1, characterized in that: The preparation method of the antistatic agent comprises the following steps: Sodium polystyrene sulfonate and dodecyltrimethylammonium bromide are dispersed in an aqueous polyurethane emulsion and stirred until the system is uniform to obtain an antistatic agent. The weight ratio of the sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and the aqueous polyurethane emulsion is 1:1:(6-9).
8. The graphite-modified polystyrene beads according to claim 7, characterized in that: The weight ratio of the sodium polystyrene sulfonate, dodecyltrimethylammonium bromide and aqueous polyurethane emulsion is 1:1:
8.
9. A method for preparing graphite-modified polystyrene beads according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: feeding graphite filler, flame retardant, antioxidant, lubricant, nucleating agent, pentane and general polystyrene, then mixing the ingredients, melt extruding, reducing pressure, pelletizing, cooling, drying, screening, and coating with an antistatic agent to obtain graphite modified polystyrene beads, wherein the melting temperature during melt extrusion is 175-190°C.
Citation Information
Patent Citations
Method for preparing high-flame-retardancy and low-thermal-conductivity graphite expandable polystyrene (EPS) bead material through polystyrene
CN104448379A
Door and window accessory heat insulation material product ultra low in heat conductivity coefficient
CN109897293A
Graphite high-temperature antioxidant capable of being quickly dried at normal temperature and application thereof
CN111825476A
Preparation method of high-temperature-resistant graphite material
CN113307264A
Silicon-containing composition for processing chlorine-containing polyolefin material and preparation method thereof
CN119529546A